Exploring hotel appraisal determinants amid sales trend during COVID-19 pandemic: using a DANP-mV model - Liu, Chui-Hua; Liu, Bochner (International Journal of Strategic Property Management, 2022)
In the current hotel sales trend due to COVID-19 pandemic, few empirical studies have discussed hotel appraisal determinants and prioritization in terms of operational efficiency. This paper presents an innovative approach for appraisal practice efficiency based on hotel appraisal approach and the multiple criteria decision making (MCDM). The DANPmV model is used to identify the determinants related to actual hotel appraisal practices, including the techniques of the decision-making trial and evaluation laboratory (DEMATEL), DEMATEL-based ANP (DANP), and modified VIKOR. The result of influential network relationship map (INRM) and the gaps of determinants to the aspiration level may contribute to improving hotel appraisal efficacy. In practice, the “discounted cash flow” becomes the most influential determinant (dimension) and the “market survey” is the most manageable one. More findings together with an action plan are presented and useful in the real world. Therefore, this innovative approach could help hotel appraisers and related parties, such as hospitality managers, investors, lenders, and decision makers, better manage the evaluation determinants of hotel appraisal efficacy.